Kemiskinan di Ende: Poverty in Ende: Anomalies of Community Empowerment and Social Assistance Programs - Ngea Andreas (LEGAL BRIEF, 2023)
This research examines the problem of poverty in Ende Regency, which has stagnated from year to year. There are a number of poverty alleviation programs that are accepted by the community, namely the Village Fund Program, the Family Hope Program (PKH), the Smart Indonesia Card and the Healthy Indonesia Card, the Red Wine Program, KUBE, Self-Help Housing Stimulant Assistance (BPSP), and PUAP assistance through Gapoktan. Meanwhile, on the other hand, there are so many funds distributed to villages through village funds with the same goal, namely to empower the community. However, the reality shows that data on the percentage of poor people has stagnated from 2018 to 2022. Departing from this problem, this research examines the poverty factor in Ende Regency. The theories relevant to dissecting the problem of poverty are the neoliberal theory of Thomas Hobbes and the theory of social democracy of Karl Marx and Frederick Engels as well as the structural-dependence theory of Andre Gunder Frank. This study uses a qualitative approach. Determination of data sources was done purposively and interviews were conducted by snowball. Meanwhile, to test the validity or correctness of facts is done by means of triangulation (testing it by using several combined methods). The results of this study concluded that, poverty alleviation programs are more social assistance than empowerment, poverty alleviation creates community dependency and program recipients seek to treat poverty so that they continue to receive assistance